176 A Retrospective Analysis of Non-Muscle Invasive Bladder Cancer (NMIBC) Follow-Up Using Flexible Cystoscopy and the Role of the Charlson Co-Morbidity Index (CCI) in Improving Follow Up. (19th August 2022) - Dickson, S; Jones, J; Clark, R
Abstract: Aim: 1. A retrospective analysis of NMIBC follow-up using flexible cystoscopy during COVID-19. 2. Charlson Co-Morbidity Index (CCI) as a method of improving follow up. Method: Online patient records were reviewed for 153 patients who attended Ayr University Hospital between 01/02/2020 and 01/05/ 2020 for check cystoscopy. We recorded the patients risk category and the number of months lapsed since their previous scope. Follow up schedules were compared with current NICE guidelines. CCI for each patient was calculated. Results: The majority of the patients sampled had follow up adherent to NICE guidelines. Deviations were secondary to 'allocation to an incorrect follow up schedule', 'late follow up' and 'non-compliance'. Incorrect allocation was due to both human error and clinical judgement. Clinical judgement included frail patients thought not to benefit from their current intensive schedule and patients with areas of suspicion warranting an earlier check. CCI scores ranged from 2–11. 25% of had a Charlson score of >6 - this predicts a 0% 10-year survival. Conclusions: We hypothesise that patients with a CCI > 6 should be considered for less intensive follow up. Their co-morbid status makes them likely unsuitable for intervention if reoccurrence was identified.We are pleased with our current adherence to NICE guidelines. We recognise areas for improvement and have raised these at local meetings. We hope that the CCI can be used to ensure we practice realistic medicine and act in the best of the patient when deciding to follow up.